PEMBELAJARAN INTEGRATIF MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM MEMBENTUK KARAKTER CINTA DAMAI DAN TANAH AIR SISWA KELAS IX MADRASAH TSANAWIYAH TARBIYATUL MUBTADIIN WILALUNG GAJAH DEMAK - Muslikin Muslikin; Achmad Maimun (Universitas Islam Madura, 2023)
Integrative learning and peace-loving character building is something that needs to be studied and researched because character is a very interesting issue to develop, thus, this study aims to analyze the design, and implementation of SKI integrative learning in building character. The research method used is qualitative and naturalistic through participant observation. Data collection techniques using observation, interviews, and documentation. The results of this study indicate: 1) Integrative learning design is structured to include strengthening character education, literacy, higher order thinking skills, and 4C (critical thinking, collaboration, communication, and creativity), 2) Integrative learning includes preliminary activities, core activities and activities closing. In integrative learning using the integration of brainstorming methods with discussions, Numbered heads together (NHT) with cooperative scripts; 3) Assessment of integrative learning outcomes includes three domains which include aspects of attitudes, aspects of knowledge, and aspects of skills. The implication of the results of this study is that integrative learning with the formation of student character can be carried out well if it is supported by all components and factors that exist in the educational circulation itself. If integrative learning is successful, then character education is also successful, and vice versa.